Comparing the effects of face-to-face and video-based educations on hand hygiene knowledge and performance among mothers in neonatal intensive care unit: A randomized controlled trial - Zhilla Heydarpoor Damanabad; Leila Valizadeh; Mohammadbagher Hosseini; Marzieh Abdolalipour; Mohammad Asghari Jafarabadi (Kashan University of Medical Sciences, 2021)
Background: Hand hygiene is the first step in nosocomial infection control. However, most people have limited knowledge about proper hand hygiene. Objectives: This study aimed at comparing the effects of face-to-face education (FTFE) and video-based education (VBE) on hand hygiene knowledge and performance among mothers in neonatal intensive care unit (NICU). Methods: Using a three-group design, this randomized controlled trial was conducted in March-December 2019 in Al-Zahra University Hospital, Tabriz, Iran. In total, 132 mothers of neonates in NICU were recruited to the study through convenient sampling and were randomly allocated to either an FTFE group, a VBE group, or a control group. Data were collected before and 3 days after the intervention using a Maternal Hand Hygiene Knowledge Questionnaire and a Maternal Hand Hygiene Performance checklist. Data analysis was performed using the Chi-square test, paired-samples t-test, one-way analysis of variance, and analysis of covariance. Results: The mean scores of hand hygiene knowledge and performance significantly increased in both the intervention groups (P < 0.05) but did not significantly change in the control group (P > 0.05). There were no significant differences among the groups regarding the pretest mean scores of hand hygiene knowledge (P = 0.24) and performance (P = 0.26), while the posttest mean scores of hand hygiene knowledge and performance in both the intervention groups were significantly greater than the control group (P < 0.05). Conclusion: Both FTFE and VBE are effective in significantly improving hand hygiene knowledge and performance among the mothers of neonates in NICU.